Sølbjerg I: An Ahrensburgian Site on a Reindeer Migration Route through Eastern Denmark - Vang, Peter; Johansen, Lykke (Journal of Danish Archaeology, 1991)
Sølbjerg I - An Ahrensburgian Site on a Reindeer Migration Route through Eastern Denmark